Applied energy and environment technologies and materials selected, peer reviewed papers from the 2014 International Forum on Applied Energy and Environment (IFAEE 2014), November 28-29, 2014, Shenzhen, China - Choi, Seung-Bok (Applied mechanics and materials, 2015)
Collection of selected, peer reviewed papers from the 2014 International Forum on Applied Energy and Environment (IFAEE 2014), November 28-29, 2014, Shenzhen, China